Shubnikov–de Haas oscillation of Bi2Te3 topological insulators with cm-scale uniformity. (19th May 2016) - Huang, Shiu-Ming; Lin, Shao-Yu; Chen, Jui-Fang; Lee, Chao-Kuei; Yu, Shih-Hsun; Chou, Mitch M C; Cheng, Cheng-Maw; Yang, Hung-Duen
Abstract: A topological insulating Bi2 Te3 single crystal was successfully grown with good uniformity using a home-made resistance-heated floated zone furnace. The temperature-dependent resistance and Hall voltage confirm that the transport is metallic and the overall carriersareholes. The angle and temperature dependence of the quantum Shubnikov–de Haas oscillation period amplitude suggests that the transport comes from the carriers of surface states. The Berry phase, determined from Landau level diagram, also reveals that the transport carriers are Dirac fermions. In contrast with many previous publications, the transport parameters relating to the surface carriers derived from the relationship of the Lifshitz–Kosevich (LK) theory are consistent with angle resolved photoemission spectroscopy results.